KEPADATAN POPULASI KEPINDING TANAH (Scotinophara coarctata) PADA TANAMAN PADI DI KENAGARIAN KOTO NAN TIGO KECAMATAN BATANG KAPAS KABUPATEN PESISIR SELATAN - Gusrianti, Eza; Jasmi, Jasmi; Indriati, Gustina (Pendidikan Biologi, 2013)
ABSTRACT One of insect pests that attack the rice plant is Scotiphara  coarctata  ( Ladybug stink ) which is more known as the bedbug ground  . This pest attacks  the rice at the beginning  of flowering  . These pests  suck fluids  book  on rice straw  that caused  crop color changed to reddish brown or yellow . In connection with that have done research on population  density  Scotinophara  coarctata  in rice on April 14 to August 15, 2013 . Sampling was conducted  in Kenagarian  Koto Nan Tigo Sub Trunk Cotton South Coastal District  descriptive  survey  method  and  collections  directly  to  Scotinophara  coarctata that existed at the study site using adhesive traps . Collection using sampling techniques ordinal decision . Decision made for 2 days in a row 2 times ( morning and afternoon ) on flowering phase and phase cook milk . Decision made on 25 clumps of rice in each phase. From  the results  of research  conducted  in the flowering  phase of the tail  with  229 gained an average of 9.16 , and the phase of the cooking milk obtained 177 tail with an average 7.08 . From the results of research conducted in Kenagarian Koto Nan Tigo Sub Trunk Cotton South Coastal District earned an average population density is 406 bedbug ground tail with an average 16.24 perpengambilan  . In this case bedbug ground already crossed a threshold .